OFSP vines multiplication and marketing in Rwanda - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
You and I Best Seed Company Ltd, a scaling partner of the AID-I GLR Project in Rwanda, deliver good agronomic practices for the OFSP value chain.